Occupational Burnout among Nurses working at Governmental Teaching Hospitals in Babylon Province, Iraq - Mansour, Hatem K; Hussien, Hassan A (International Journal of Psychosocial Rehabilitation, 2020)
Aimed this study to be assessed the level burnout among nurses and found the relationship between occupational burnout socio-demographic of responders. The study Initiated from (September 2019 to March 2020), The research design was employed in this study a descriptive design. The sampling of this study was the purposive sample by 180 nurses working in four governmental teaching hospitals in Babylon province, Iraq. The results of data analysis was employed by Statistical Package for Social Science (SSPS version 24) that found burnout levels of the study sample (57.8%) a moderate level of burnout and subdomain burnout levels results was (57.8%) of sample moderate level for emotional exhaustion and the depersonalization ( 61.1%) moderate level. However, Personal Achievement was reported (61.1%) high level score, as well there was significant difference between occupational burnout and number of experience in nursing, so there was no relationship between, material states and burnout. However, there was association between burnout level and income monthly, job description and degree of satisfied with current work. The researchers found that burnout impact on nurses and correlated negatively with some their socio-demographic characteristics and they recommended to enhance nurse's stress coping.